2021
DOI: 10.1039/d1ra06845h
|View full text |Cite
|
Sign up to set email alerts
|

Composite photocatalysts based on Cd1−xZnxS and TiO2 for hydrogen production under visible light: effect of platinum co-catalyst location

Abstract: The determination of the preferred location of platinum particles in TiO2–Cd1−xZnxS systems was carried out for the first time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 74 publications
0
4
0
Order By: Relevance
“…Another study by Shi et al for rutile titanium dioxide nanowires through the chemical vapor deposition technique showed nanorod morphology and expressed high crystallinity and large surface area . Further, cadmium zinc sulfide composite with titanium dioxide heterostructure synthesized via chemical vapor deposition showed a hydrogen production rate of 26 mmol g –1 h –1 , which was exceeded 20% more than that of the same composite with a platinum heterojunction . The hydrogen evolution was studied in an alkaline solution of triethanolamine and sodium hydroxide, and the concentration was measured by gas chromatograph .…”
Section: Synthesis Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Another study by Shi et al for rutile titanium dioxide nanowires through the chemical vapor deposition technique showed nanorod morphology and expressed high crystallinity and large surface area . Further, cadmium zinc sulfide composite with titanium dioxide heterostructure synthesized via chemical vapor deposition showed a hydrogen production rate of 26 mmol g –1 h –1 , which was exceeded 20% more than that of the same composite with a platinum heterojunction . The hydrogen evolution was studied in an alkaline solution of triethanolamine and sodium hydroxide, and the concentration was measured by gas chromatograph .…”
Section: Synthesis Methodsmentioning
confidence: 99%
“…The present application of CVD includes extraction and pyrometallurgy, electronic and optoelectronic materials, surface modification and coatings, ceramic fibers, and ceramic matrix composite synthesis. The advantages of the CVD process consist of high-purity material, good reproducibility, good deposition rate, and better control of morphology and crystal structure. Besides, it has some drawbacks toward safety as it uses corrosive flammable and toxic gases as precursors and is difficult to deposit on a multicomponent material with controlled geometry . An et al reported on nanostructured titanium-based thin films with controlled morphology using titanium isopropoxide, bis­(ethyl cyclopentadienyl) nickel, and other precursors showing tubular and branched tree shape .…”
Section: Synthesis Methodsmentioning
confidence: 99%
See 2 more Smart Citations